Kemampuan Ukuran Perusahaan Memoderasi Pengaruh Capital Adequacy Ratio dan Loan To Deposit Ratio pada Profitabilitas Bank di Bursa Efek Indonesia - Setiyoso, Annys Asrofah; Suardana, Ketut Alit (E-Jurnal Akuntansi; Vol 33 No 6 (2023), 2023)
This study aims to obtain empirical evidence of the effect of the Capital Adequacy Ratio and Loan to Deposit Ratio on profitability moderated by company size in banking companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling and 45 observation samples were obtained. Moderated Regression Analysis is used as a data analysis technique. The results showed that the Capital Adequacy Ratio and Loan to Deposit Ratio had a positive and significant effect on profitability and firm size were able to strengthen the positive influence of the Capital Adequacy Ratio and Loan to Deposit Ratio on the profitability of banks listed on the Indonesia Stock Exchange. This means that the higher the capital adequacy ratio and liquidity ratio, the higher the company's profitability, the higher the capital adequacy ratio and liquidity ratio, which are accompanied by an increase in assets, the higher the profitability. Keywords: Capital Adequacy Ratio; Loan to Deposit Ratio; Profitability; Firm Size